Effectiveness of Various Fertilizers on Hybrid Corn (Zea mays L.) in Dry Land - Neni Marlina; Berliana Palmasari; Ananda Yogi; Sutarmo Iskandar; Haris Kriswantoro; Yani Purwanti; Firnawati Sakalena (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Dry land has significant potential for cultivating hybrid corn. However, its limitations include water scarcity, poor soil physical properties, and limited availability of NPK nutrients. To improve dryland conditions, organic fertilizers, inorganic fertilizers, and organic fertilizers enriched with phosphate-solubilizing bacteria can be applied. The use of organic fertilizers—such as chicken manure and empty oil palm bunches (tankos)—as well as organic fertilizers enriched with phosphate-solubilizing bacteria, can enhance soil quality by improving its physical structure (making the soil looser and more fertile) and chemically increasing nutrient availability, thereby supporting better growth and yield of hybrid corn plants. This study aimed to evaluate the effectiveness of various fertilizer types on the growth and productivity of hybrid corn cultivated on dry land. The field experiment was arranged in a randomized complete block design (RCBD) with four treatments, each replicated six times: recommended chemical fertilizers (A), chicken manure fertilizer (B), organic fertilizer enriched with phosphate-solubilizing bacteria (C), and empty oil palm bunches (tankos) fertilizer (D). The highest yield was achieved using the recommended chemical fertilizer, producing 3.42 kg per plot (13.68 tons per hectare). The second highest yield was obtained with organic fertilizer enriched with phosphate-solubilizing bacteria, yielding 2.98 kg per plot (11.92 tons per hectare). The third-highest yield came from chicken manure fertilizer, producing 2.67 kg per plot (10.68 tons per hectare), followed by tankos fertilizer at 2.2 kg per plot (8.8 tons per hectare). The novel finding of this study is that organic fertilizer enriched with phosphate-solubilizing bacteria, without the addition of inorganic fertilizers, can achieve yields comparable to those obtained with recommended chemical fertilizers. While inorganic fertilizers are effective in increasing hybrid corn yields in the short term, their long-term use may negatively impact the environment and soil fertility. Therefore, organic fertilizer enriched with Azospirillum bacteria presents a more environmentally friendly and sustainable alternative.